Urban typologies and heat energy demand. A case-study in the Italian context - Elisabetta Troglio; Tigran Haas; Matteo Doni (European Regional Science Association (ERSA), 2011)
Nowadays, large parts of the world population (50-60%) are living in urban areas, which represent the most energy consuming systems (Buckley et al., 2009). Local governments are therefore asked to take new responsibilities in terms of energy management, adopting the urban scale as level of action, developing new methods and strategies to bring energy sustainability (saving/producing) and environmental quality into the cities. The development of a new energetic and environmental planning approach that can set energy as primary key - leading to a high level of urban efficiency and having a broad effect on other urban areas - is hence highly important. Different studies have pointed out the fundamental energetic role of urban morphology and typology (Ratti et al., 2004). Recognizing the key role of planning and design, and the contribution of modeling, some questions are arising: is it possible to analyze the performances of the built environment in a georeferenced way, considering the effect of urban design/form aspects, in order to achieve a better knowledge of those city characteristics that influence energy demand? Which is the role played by typologies in (re)orienting the energy analyses/model? Which targets can be achieved in reducing cost and energy? The project explore different factors involved in the energy performance of the city, in particular using an innovative evaluation model of heat energy demand, which has urban typologies as starting and key point of the analyses. A dynamic and georeferenced method has been specifically developed, allowing the estimation of the energy behavior of the "real" city. The empirical study is applied at the City of Gorgonzola - Italy, which holds potential both for the dimension of the built environment and the variety of urban typologies, which allow a comparison between them. Purpose of the paper is thus to analyze the results coming from the estimation, that can lead to a strong integration between energy, urban design and planning system.
Keywords: 330